Short term load forecasting at Pulau Perhentian using ANN / Mohd Khusairi Ali - Ali, Mohd Khusairi (2013)
Short term load forecasting is the one of the important thing in power system planning, operating and control. Load forecasting can use the Artificial Neural Network (ANN). This ANN trained based on weather component.